About Petar Bogdani, don Luka Jelić and Croatian-Albanian Cultural Contacts - Vinicije B. Lupis; Elvis Shala (Peristil)
The authors deal with several insufficiently explored Croatia‒Kosovo cultural relations through the prism of Dubrovnik’s connections with Albanian areas and Kosovo. In the context of archbishop Petar Bogdani's personal idiosyncrasy in the 17th century, the authors point out the cultural framework of recording the first Roman inscriptions in Shkoder, as well as modern and medieval epigraphs in Albania and Kosovo, and inscriptions from the Church of Saint Sergius and Bacchus on the Bojana River.